(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article about Religious terms in the English language represent a vibrant intersection of linguistic, cultural, and historical evolution. The study of these terms offers valuable insights into how religion shapes language and vice versa. This paper explores the linguistic features of religious terminology in English, focusing on their etymology, semantic characteristics, morphological patterns, and pragmatic functions. Additionally, it highlights how religious concepts evolve with time and become part of everyday language, reflecting both sacred and secular influences.